Experimental and numerical investigations on NOx formation and reduction mechanisms of pulverized-coal stereo-staged combustion. (15th December 2022) - Zeng, Guang; Zhou, Anqi; Fu, Jinming; Ji, Yang
Abstract: With the gradual increase of intermittent renewable energy, the coal-fired power generating units must provide flexible peak shaving capabilities. However, the new requirement comes with increasing challenges for the pulverized coal utility boilers, as it tends to have lower combustion efficiency and higher NOx emission at extremely low loads. Accordingly, this work aims at coupling the NOx formation and reduction mechanisms with computational fluid dynamic simulation to thoroughly explore the technology for NOx abatement. The effect of the different primary air equivalence ratios on the Whitehaven bituminous combustion was experimentally and numerically studied. The combustion experiments were performed in a down-fired facility. Moreover, the numerical model validated well with the experimental results. The results reveal that, by reducing the primary air equivalence ratio, the combustion efficiency of pulverized coal stereo-staged combustion increased. Furthermore, the formation and reduction rate of fuel-NOx by HCN decreased but those by NH3 slightly increased. In addition, the fuel-NOx reaction rates from char-nitrogen decreased. The NH 3 was oxidized to NOx, while HCN mainly played the role of reducing NOx . The primary air equivalence ratio of 0.24–0.28 was found to be the optimal range for the pulverized coal stereo-staged combustion technology. Highlights: The HCN and NH3 formations decreased as the primary air equivalence ratio decreased. The combustion efficiency increased as the primary air equivalence ratio decreased. NH3 was oxidized to NOx and HCN mainly played the role of reducing NOx . The primary air equivalence ratio of 0.24–0.28 is conducive to lowering NOx .